Operational DGT threshold values for metals in seawater from protected coastal areas in Sardinia (Western Mediterranean). (January 2020) - Marras, Barbara; Montero, Natalia; Marrucci, Alessandro; Bettoschi, Alexandre; Atzori, Marco; Schintu, Marco
Abstract: Diffusive gradients in thin films (DGTs) were used for monitoring metal (Cd, Cu, Ni, and Pb) concentrations in protected and non-protected coastal areas in Sardinia (Western Mediterranean). The deployment of DGTs in relatively undisturbed areas enabled calculation of operational DGT threshold values, which can be used for assessments of the environmental quality of coastal areas. The DGT thresholds were defined as the median metal concentrations that were found in protected areas, which ensured consideration of the natural variability of the different study sites. The calculated DGT thresholds were 11.6 ng L −1 for Pb, 5.1 ng L −1 for Cd, 63 ng L −1 for Cu and 152 ng L −1 for Ni. A comparison of the calculated DGT thresholds with previous DGT studies in the area demonstrated their suitability for identifying sites of environmental concern in the Western Mediterranean. Highlights: First operational DGT thresholds for the Western Mediterranean were established. DGT metal concentrations were measured in a variety of coastal sites in Sardinia. Metal concentrations in protected areas were used to calculate DGT thresholds. Contamination degree of coastal areas can be assessed using calculated thresholds. This approach could be extended to other coastal areas in the Mediterranean.